ChemInform Abstract: Transport Properties of APdCu(Se2)(Se3) (A: K and Rb): New Quaternary Copper Palladium Polyselenides. Issue 39 (23rd September 2014) - Azam, Sikander; Reshak, A. H.
Abstract The electronic structure, effective mass, optical properties, and electrical transport coefficients of the title compounds are investigated by DFT calculations.